Insight from Nunavut Educators Using Appreciative Inquiry (Alberta Journal of Educational Research, 2017)
The purpose of this paper is to document some successful features of public schools within Nunavut, according to the personal experiences of a group of 14 principals, vice-principals, and teachers. At the start of this paper, I explained my research positionality, depicting my personal history and background related to this study. From a total of 24 individual interviews, three themes surfaced: culturally vibrant programs, the array of professional development offered to educators, and student self-pride and involvement in school activities. To conceptualize the findings, I applied the 4-D cycle of appreciative inquiry (i.e., Discovery, Dream, Design, and Destiny) and explained how effective change can emerge within a school system. Appreciative inquiry is a change process of identifying what is working well, deciphering why it is working well, and emulating more of those positive attributes.L’objectif de cet article est de documenter quelques-unes des caractéristiques des écoles publiques au Nunavut qui - selon les expériences personnelles d’un groupe de 14 personnes composé de directeurs, directeurs adjoints et d’enseignants - sont les mieux réussies. Je commence par expliquer mon positionnement comme chercheuse, évoquant ainsi mon histoire et mes antécédents personnels par rapport à cette étude. Trois thèmes ressortent des 24 entrevues individuelles : des programmes dynamiques sur le plan culturel, des possibilités en matière de développement professionnel pour les enseignants, et l’orgueil des élèves et leur et la participation aux activités scolaires. Pour présenter les résultats, j’ai appliqué la démarche des 4D de l’enquête appréciative (c.-à-d. découverte, devenir, décision, déployer) et j’ai expliqué comment le changement peut véritablement avoir lieu au sein d’un système scolaire. L’enquête appréciative est un processus de changement qui consiste à identifier les éléments qui fonctionnent bien, comprendre les raisons de leur efficacité et imiter davantage de ces aspects positifs.